Analisa Statistika Untuk Curah Hujan Harian Pada Das Kampar Berdasarkan Aic (Akaike Imformation Criterion) - Citra Dewi Simbolon; Bambang Sujatmoko; Mardani Sebayang (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The applicability of the frequency distributions had been widely used for the analysis of daily rainfall because the rain had different characteristic according to space and time. Distributions were often used for example gamma distribution, exponential, normal, log normal, Gumbel, and log the third person. This research aims to election statistics for rainfall distribution based on AIC and to determine which one was most appropriate distribution based on the Chi-kuardrat test and Kormologrov Smirnov test. The distributions in this research were searched maximum likelihood value, then evaluated based on the value of the Akaike Information Criterion (AIC). Maximum likelihood estimate of the value was used to maximize the distribution parameters in AIC. Distribution which has the smallest AIC value that will be used for the Chi Square test and Kolmogorov- Smirnov test. Research result shows all stations in the Kampar river basin, generate normal distribution that has the smallest AIC value. For Chi Square test and Kolmogorov-Smirnov test showed a normal distribution can be accepted in the watershed Kampar. Keywords: Akaike Information Criterion, Chi Square, exponential distribution gamma distribution, Gumbel distribution, normal distribution, log normal distribution, log the third person distribution, Kolmogorov-Smirnov